HUBUNGAN PENGETAHUAN DAN KEPATUHAN IBU HAMIL DENGAN PEMANFAATAN BUKU KESEHATAN IBU DAN ANAK (KIA) - Turiyani; Meriaya Sari, Lely; Melsiyani (Jurnal Kesehatan dan Pembangunan, 2025)
The mother and child health book is a book that contains mother's health records starting from pregnancy, childbirth to postpartum, apart from that, the KIA book also contains children's health records, from newborns to 6 year old children. This study aims to determine the relationship between knowledge and compliance of pregnant women with the use of maternal and child health books. This research uses analytical methods, with a cross sectional approach. The population was all third trimester pregnant women who visited Umi Kalsum's independent practice when the research was conducted. The sample consisted of 40 people taken by accidental sampling, with a questionnaire as the research instrument. The research results based on univariate analysis were obtained from 40 people, there were 32 people (80%) who used the KIA book and 8 people (20%) who did not use the KIA book, there were 31 people (77.5%) who had good knowledge and 9 people ( 22.5%) had less knowledge, there were 30 people (75%) who complied with ANC visits ? 4 times and 10 people (25%) who made ANC visits < 4 times. And from the results of the Bibariat analysis, it was found that of the 31 people who had good knowledge, 29 people (72.5%) used the KIA book, while of the 9 people who had less knowledge, 3 people (7.5%) used the KIA book. Of the 30 people who complied with ANC visits ? 4 times, 28 people (70%) used the KIA book, while of the 10 people who made ANC visits < 4 times, 4 people (10%) used the KIA book. The conclusion is that there is a significant relationship between knowledge and the use of KIA books with a P value of 0.000 and there is a significant relationship between maternal compliance and the use of KIA books with a P value of 0.001.